PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL RECIPROCAL TEACHING PADA SISWA KELAS IV SEKOLAH DASAR - afrina, fitri; Mahyuddin, Ritawati; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this study is to describe the improvement of reading comprehension skill of the 4th-grade students of Elementary School No.23 Marapalam, Padang with the use of Reciprocal Teaching strategy. This study is classroom action research that uses qualitative and quantitative approaches. The result showed that students’ reading comprehension ability increased from 64,98 (Fair) with 31,25% level of mastery in cycle I, to 87,88 (Very good) with 90,62% level of mastery in cycle II. The percentage of improvement from cycle I to cycle II is 22,9%. Based on these results, it is concluded that Reciprocal Teaching strategy significantly improves the reading comprehension ability of the 4th-grade students of Elementary School No.23 Marapalam, Padang. Keywords: read comprehension ability; Reciprocal Teaching strategy; Elementary school students